Prospective, pilot evaluation of the performance of nanofractional radiofrequency for improvement of skin texture via skin resurfacing. (31st October 2017) - Bohnert, Krista; Dorizas, Andrew; Sadick, Neil
Summary: Background: The latest generation of radiofrequency, nanofractional radiofrequency, allows the heat energy to be delivered through the use of pins or needles as electrodes, facilitating increased efficacy and reduced pain, downtime, and side effects. Objective: The objective of this prospective pilot clinical study was to evaluate the efficacy of nanofractional radiofrequency in skin resurfacing. Methods and materials: Seventeen subjects were enrolled in the study, and each received three nanofractional radiofrequency (160‐pin tip) treatments in the facial area at 3‐week intervals. Follow‐up visits were scheduled at 1 and 2 months after the final treatment. Clinical photography, patient, and investigator assessments were conducted during the treatment visits and follow‐up. Results: All subjects completed the study. At the 1‐ and 2‐month follow‐up, there was a moderate to significant improvement (2.6 and 3.5, respectively, P = .01) according to the investigator global esthetic improvement scale rating. Most subjects reported that they were satisfied or very satisfied with the outcome and level of comfort. Conclusion: Nanofractional radiofrequency is a safe and effective strategy for improving texture, tone, and skin laxity with high patient satisfaction and tolerable safety profile.